Concurrent Imaging of Markers of Current Flow and Neurophysiological Changes During tDCS - Jog, Mayank; Jann, Kay; Yan, Lirong; Huang, Yu; Parra, Lucas; Narr, Katherine; Bikson, Marom; Wang, Danny J. J. (Frontiers in Neuroscience, 2020)
Despite being a popular neuromodulation technique, clinical translation of transcranial direct current stimulation (tDCS) is hampered by variable responses observed within treatment cohorts. Addressing this challenge has been difficult due to the lack of an effective means of mapping the neuromodulatory electromagnetic fields together with the brain’s response. In this study, we present a novel imaging technique that provides the capability of concurrently mapping markers of tDCS currents, as well as the brain’s response to tDCS. A dual-echo echo-planar imaging (DE-EPI) sequence is used, wherein the phase of the acquired MRI-signal encodes the tDCS current induced magnetic field, while the magnitude encodes the blood oxygenation level dependent (BOLD) contrast. The proposed technique was first validated in a custom designed phantom. Subsequent test-retest experiments in human participants showed that tDCS-induced magnetic fields can be detected reliably in-vivo. The concurrently acquired BOLD data revealed large-scale networks characteristic of a brain in resting-state as well as a ‘cathodal’ and an ‘anodal’ resting-state component under each electrode. Moreover, ‘cathodal’s BOLD-signal was observed to significantly decrease with the applied current at the group level in all datasets. With its ability to image markers of electromagnetic cause as well as neurophysiological changes, the proposed technique may provide an effective means to visualize neural engagement in tDCS at the group level. Our technique also contributes to addressing confounding factors in applying BOLD fMRI concurrently with tDCS.